Tips and Tricks on Paravalvular Leak Closure after Aortic Valve Replacement and Transcatheter Aortic Valve Implantation (TAVI): A Case Series - Onorato, Eustaquio Maria; Vercellino, Matteo; Costante, Annamaria; Bartorelli, Antonio L.; Evola, Salvatore; D’Agostino, Alessandro; Adorno, Daniele; Triolo, Oreste Fabio; Giarratana, Gioacchino (Medical Science: Trends and Innovations Vol. 3, 2025)
Background: Paravalvular leak (PVL) after surgical valve replacement (AVR) and after Transcatheter Aortic Valve Implantation (TAVI) is an ominous complication with a high risk of morbidity and mortality. Approximately 1–5% of PVLs can lead to serious clinical consequences, including congestive heart failure and/or hemolytic anemia. Aim: The aim of the study is to explore effective techniques and strategies for closing paravalvular leaks (PVLs) after Aortic Valve Replacement and after Transcatheter Aortic Valve Implantation. Case Series: 1) A 69-year-old man with multiple comorbidities underwent surgical replacement of the aortic valve with a mechanical tilting disc prosthetic valve (Medtronic Starlight 27 mm). Several years later, recurrent episodes of congestive heart failure and hemolytic anemia developed due to a large crescent-shaped aortic PVL located at non-coronary cusp (NCC) 9–12 o’clock, with moderate-to-severe regurgitation. The huge PVL was partially closed by the first specifically designed paravalvular leak device (PLD). The procedure was complicated by transient interference of the second PLD with mechanical prosthetic valve function. This issue has however been solved with correct manipulation, orientation and downsizing of the second device implanted. 2) An 85-year-old woman suffering from long-standing atrial fibrillation and severe symptomatic aortic stenosis underwent SE TAVI (26 mm EvolutTM R®, Medtronic Inc., MN, USA). Eighteen months after TAVI, she was admitted for congestive heart failure and two-dimensional (2D) transesophageal echocardiography (TEE) color Doppler showed moderate-severe PVL regurgitation due to a long and heavily calcified leak located below the left coronary sinus. During transcatheter PVL closure (TPVLc), an extra arterio-arterial (AA) support loop and Intravascular lithotripsy (IVL) application greatly facilitates the progression of the delivery sheath and occluder resulting key to the success of the procedure. Discussion: Surgical redo has been considered the treatment of choice for symptomatic patients with PVLs. Notwithstanding, TPVLc after AVR and after TAVI is a less invasive alternative, particularly in patients at high surgical risk, where early diagnosis and prompt interventional treatment are crucial for improving expectancy and quality of life. Dedicated devices, appropriate procedural techniques, and the close interaction between imaging modalities allowed to deal successfully with challenging cases of severe symptomatic aortic PVL regurgitation. Conclusion: Transcatheter aortic PVL closure is a feasible, safe, less invasive and life-saving alternative to surgical repair, particularly in patients deemed at high risk for redo surgery.